Exclusive Breastfeeding Promotion on Young Breastfeed Mother - Andi Julia Rifiana; Rizqi Nursasmita; Amanda Sarah Putri (Rajaki of Tulip Medika Publisher, 2025)
Background: Infants receiving exclusive breastfeeding have a lower risk of excessive weight or obesity and a lower risk of long-term diseases. The success of breastfeeding is influenced by the mother's readiness, both physically and mentally. In DKI Jakarta, according to SSGI, the percentage of exclusive breastfeeding coverage is 45.9%. The highest coverage of exclusive breastfeeding in the DKI Jakarta Province is in South Jakarta at 79.16%, while the lowest is in East Jakarta at 47.25%. Purpose: This research aims to analyze the need for exclusive breastfeeding education in among breastfeeding mother Method: This research used a qualitative method with a phenomenological approach. The research design involves in-depth interviews to gather further information about the knowledge of mothers in providing exclusive breastfeeding, their attitudes, and family support for the breastfeeding process. Results: Informants have knowledge about exclusive breastfeeding, but most informants do not know until how many months exclusive breastfeeding should be given. The informants' knowledge about the benefits of colostrum is very limited, indicating a need for deeper education on colostrum and exclusive breastfeeding knowledge. Conclusion: The lack of knowledge among mothers about exclusive breastfeeding, and most breastfeeding mothers face common challenges during the breastfeeding process.